(untitled) (International Journal of Food and Nutritional Sciences, 2022)
According to the World Health Organization (2005), approximately 10% of the world’s population has a disability, and 80% of those with disabilities live in the developing world. Since the mid-twentieth century, there has been a growing international disability movement that has pushed for the inclusion of people with disabilities within society. Countries have developed policies related to education, employment, income support, and anti-discrimination to improve the position of people with disabilities within their own society. This is sometimes based on international agreements and programmes, such as the United Nations Declaration on the Rights of Disabled Persons of 1975 (United Nations, 1975), UNCRPD (United Nations 2006). However, for policies and programmes to be effective, it is important that they take into account the cultural beliefs about disability that exist within their populations. This study explores the cultural beliefs of people towards the disability in Indian set up, and the impacts of such beliefs on the implementation of disability policy and focus on new role of teachers for successful implementation of Inclusive education. India is a country with all level policies promoting community inclusion and inclusive education. Despite these policies, people with disabilities are often excluded from schools and community life.